2017
DOI: 10.1128/aem.01400-17
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Genes Comprising the Locus of Heat Resistance in Escherichia coli

Abstract: The locus of heat resistance (LHR) is a 15- to 19-kb genomic island conferring exceptional heat resistance to organisms in the family , including pathogenic strains of and The complement of LHR-comprising genes that is necessary for heat resistance and the stress-induced or growth-phase-induced expression of LHR-comprising genes are unknown. This study determined the contribution of the seven LHR-comprising genes, ,, ,, , and by comparing the heat resistances of strains harboring plasmid-encoded derivatives of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 33 publications
1
38
1
Order By: Relevance
“…A high proportion of chlorine-resistant isolates of E. coli recovered from wastewater also harbor the locus of heat resistance (LHR) (9), a genomic island that mediates extreme heat resistance in E. coli (17). The genes on the LHR are predicted to encode proteins associated with responses to heat shock, cell envelope stress, and oxidative stress (18). The putative mechanisms of LHR-mediated heat resistance (18) overlap the chlorine resistance mechanisms (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A high proportion of chlorine-resistant isolates of E. coli recovered from wastewater also harbor the locus of heat resistance (LHR) (9), a genomic island that mediates extreme heat resistance in E. coli (17). The genes on the LHR are predicted to encode proteins associated with responses to heat shock, cell envelope stress, and oxidative stress (18). The putative mechanisms of LHR-mediated heat resistance (18) overlap the chlorine resistance mechanisms (Fig.…”
mentioning
confidence: 99%
“…The genes on the LHR are predicted to encode proteins associated with responses to heat shock, cell envelope stress, and oxidative stress (18). The putative mechanisms of LHR-mediated heat resistance (18) overlap the chlorine resistance mechanisms (Fig. 1).…”
mentioning
confidence: 99%
“…Also upregulated were several sulfate transporters, and the potassiumefflux system protein KefB. Of relevance, kefB belongs to the locus of heat resistance in E. coli (Mercer et al, 2017) and it has been studied for its ability to acidify intracellular pH in response to electrophilic stress (Ferguson et al, 1995). Pdd is one of the few urease-producer species within the Vibrionaceae family, and genes encoding urease subunits were upregulated at human body temperature.…”
Section: Growth At 37 • C Triggers a Strong Stress Response: Heat Shomentioning
confidence: 99%
“…The LHR increases the D 60 value (decimal reduction time [i.e., the time required to kill 90% of the microorganisms] at 60°C) relative to that of LHR-negative strains of the same species 10-to 100-fold (13). LHR-encoded proteins include heat shock proteins that prevent or repair protein misfolding and aggregation (14,15). Both the LHR and the spoVA 2mob operon are mobile genetic elements and may transfer to pathogenic bacteria or spoilage organisms; therefore, heat resistance provided by the LHR and the spoVA 2mob operon challenges the control of pathogens in food system by thermal processing (13,16).…”
mentioning
confidence: 99%
“…Previous studies mainly demonstrated the mechanisms of functional genes mediating heat resistance (6,7,14,23), but the environmental selective pressure for heat resistance genes in natural and human-made ecosystems remains unclear. Therefore, this study aimed to investigate the environmental selective pressure for heat-resistant organisms in food fermentation.…”
mentioning
confidence: 99%